2016
DOI: 10.7448/ias.19.1.20659
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B and C viruses in HIV‐positive patients in China: a cross‐sectional study

Abstract: IntroductionLiver disease related to hepatitis B (HBV) and hepatitis C (HCV) may temper the success of antiretroviral therapy (ART) in China. Limited data exist on their prevalence in HIV-positive Chinese. A multi-centre, cross-sectional study was carried out to determine the prevalence and disease characteristics of HBV and HCV co-infection in HIV-positive patients across 12 provinces.MethodsHIV-positive ART-naïve patients were recruited from two parent cohorts established during November 2008–January 2010 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 34 publications
3
46
0
1
Order By: Relevance
“…For example in Vietnam, the prevalence of chronic HBV in HIV-infected individuals who inject drugs or who are sex workers (SW), is 28% and 15% respectively [50] . The prevalence of HIV-HBV co-infection overall in China has been estimated at 10% but varies between regions from 5 to 15% [25] . Accurate data are still lacking for coinfection in many parts of the world, however rates appear to be highest in parts of West and South Africa (Figure 1).…”
Section: Epidemiologymentioning
confidence: 99%
“…For example in Vietnam, the prevalence of chronic HBV in HIV-infected individuals who inject drugs or who are sex workers (SW), is 28% and 15% respectively [50] . The prevalence of HIV-HBV co-infection overall in China has been estimated at 10% but varies between regions from 5 to 15% [25] . Accurate data are still lacking for coinfection in many parts of the world, however rates appear to be highest in parts of West and South Africa (Figure 1).…”
Section: Epidemiologymentioning
confidence: 99%
“…With increasing access to antiretroviral therapy (ART), the burden of viral hepatitis in resource limited settings is expected to increase as is now the case in Europe and North America [11, 12]. There is therefore the concern that if this is not addressed, hepatitis virus related disease may threaten the success of ART programs in developing countries [12].…”
Section: Introductionmentioning
confidence: 99%
“…There is therefore the concern that if this is not addressed, hepatitis virus related disease may threaten the success of ART programs in developing countries [12]. Understanding the prevalence and disease characteristics of HBV and HCV coinfection with HIV is thus essential [13].…”
Section: Introductionmentioning
confidence: 99%
“…We observed that one-third of the HIV-infected patients were living with liver fibrosis before ART and the majority of them had attenuated or stabilized liver fibrosis after ART. In a multicenter cross-sectional study of HIV-positive ARTnaïve patients across twelve provinces in China, the proportion of participants with liver fibrosis or FIB-4 ≥ 1.45 was 26.2% (12). Recently, Ding et al reported that the prevalence of liver fibrosis was as high as 42.5% among 3900 HIV-infected ART-naïve patients in OR, odds ratio; CI, confidence interval.…”
Section: Discussionmentioning
confidence: 99%
“…In China, common risk factors for liver disease such as alcohol use, HBV and HCV infections are more prevalent in HIV-infected patients than those without HIV infection (9)(10)(11)(12). All-cause mortality was also higher in HIV-infected patients with HBV and/or HCV coinfection(s) than in those with HIV only, although ART has generally increased life expectancy of HIV-infected patients (13).…”
Section: Introductionmentioning
confidence: 99%